How does allocation of emotional stimuli impact working memory tasks? An overview - Ribeiro, Fabiana Silva (2019)
In this review, we investigated the influence of happy/pleasurable and sad/unpleasant emotional stimuli on working memory (WM) performance. Twenty-eight out of 356 articles were reviewed. We observed that emotional stimuli were used as mood inductors or as targets comprising the WM task. Results showed that WM modalities were influenced differently when updating, interference resolution, span, and complex tasks were applied. Specifically, we found distinct effects of emotional stimuli for updating tasks, in which (a) verbal modality seems to be impaired regardless of the emotional valence used compared to neutral stimuli, (b) visual updating processes appear to be improved by emotional stimuli as the targets of the task, and (c) emotional words improved interference resolution performance. As for storage, span, and complex WM tasks, sad/unpleasant emotional stimuli seem to decrease both verbal and visuospatial modalities when used as emotional inductors.